PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI THE HILL HOTEL DAN RESORT SIBOLANGIT - Selly Evianta; Lusiah Lusiah; Ripka Seriidahnaita Ginting (JURNAL CAFETARIA, 2022)
This research uses quantitative descriptive research methods. The population in this study were guests staying at The Hill Hotel & Resort Sibolangit and a study sample of 60 people using the non-probability sampling technique method. The data analysis technique uses classical assumption tests, multiple linear regression analysis, f-tests, t-tests, and coefficients of determination. The results showed that significantly the dimension of service quality affects customer satisfaction. Although the assurance dimension shows an insignificant influence on customer satisfaction, the other four variables that shape service quality, namely tangible, realibility, responsiveness and emphaty, show a significant influence on customer satisfaction. The magnitude of the coefficient of determination of 0.571 means that the ability of the variables tangible, reliability, responsiveness, assurance and emphaty explains its effect on the customer satisfaction variable of 57.1%. While the remaining 42.9% is another free variable that was not studied in this study such as competence, courtesy, communication, credibility, security and others. The conclusion states that simultaneously, the dimension of service quality has a positive effect on customer satisfaction.